Dual confinement of carbon/TiO2 hollow shells enables improved lithium storage of Si nanoparticles. (10th March 2021) - Wang, Kai; Li, Ningning; Xie, Jiayue; Lei, Guanglu; Song, Changde; Wang, Shixin; Dai, Penghao; Liu, Xianghong; Zhang, Jun; Guo, Xiangxin
Highlights: A yolk-shell structure of carbon@TiO2 @Si (CTS) is designed by a template process. Si nanoparticles are confined in the carbon/TiO2 double shells with abundant void space. The yolk-shell architecture improves the structure stability of the electrodes. The CTS delivers a high capacity and good cycling performances. Abstract: Silicon is regarded as one of the most promising anode materials for next generation lithium-ion batteries (LIBs). However, the severe volume changes during lithiation/delithiation, leading to fast capacity decay and reduced cycling life, remains an obstacle to its practical application. In this work, we propose the design of a yolk-shell structure of carbon@TiO2 @Si (CTS) by template process based on sol-gel chemistry. The Si nanoparticles are confined in the carbon/TiO2 double shells with abundant void space between the Si core and carbon/TiO2 shells. The yolk-shell architecture with concentric double shells substantially improves the structure stability of the electrodes. Consequently, the CTS delivers a high capacity of 747 mA h g −1 at a current density of 100 mA g −1, which is far superior to that (356 mA h g −1 ) of C@Si (CS) with only a single carbon shell. The double-shelled confinement strategy proposed in this work sheds some light on the development of improved Si-based anode for next-generation LIBs. Graphical abstract: A yolk-shell structure of carbon@TiO2 @Si is designed by a template process based on sol-gel chemistry and shows substantially improved electrochemical properties as an anode for lithium-ion batteries. Image, graphical abstract